2018
DOI: 10.4236/fns.2018.98069
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Extraction Method on Physicochemical Characteristics and Antioxidant Potential of <i>Adansonia digitata</i> Oil

Abstract: In this study, the effect of extraction processes on the physicochemical characteristics and antioxidant potential of baobab (Adansonia digitata L.) seed oil was evaluated. The oils were extracted, on the one hand, by cold pressing, and on the other hand, with three types of organic solvents (acetone, chloroform, n-hexane). The recorded results indicated that the extraction yield of baobab oil was significantly impacted by both the extraction method and the polarity of the solvent used. In addition, chloroform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…Variation in seed oil oxidative stability with extraction technique was also reported in the studies of Cavdar et al. (2017) , Cissé et al. (2018) and He et al.…”
Section: Processing Factors Affecting Quality Attributes Of Edible Frmentioning
confidence: 54%
See 1 more Smart Citation
“…Variation in seed oil oxidative stability with extraction technique was also reported in the studies of Cavdar et al. (2017) , Cissé et al. (2018) and He et al.…”
Section: Processing Factors Affecting Quality Attributes Of Edible Frmentioning
confidence: 54%
“…Therefore the authors concluded that temperature, pressure and extraction time are critical factors in determining the antioxidant capacity of seed oil from subcritical and supercritical fluid extractions. Cissé et al. (2018) compared the antioxidant activity of baobab seed oil extracted by mechanical pressing and solvent extraction using acetone, chloroform and hexane.…”
Section: Processing Factors Affecting Quality Attributes Of Edible Frmentioning
confidence: 99%
“…Since the beginning of the 2000s, an important research effort has been made to study different varieties of African wild fruits. In Senegal, studies have shown the nutritional potential of fruits of plant species such as baobab (Adansonia digitata) [2,3], bissap (Hibiscus sabdariffa) [4,5], and ditax (Detarium senegalense) [6]. These fruits are very popular in African gastronomy, and fit into the formulations of different food products put on the market by local processors.…”
Section: Introductionmentioning
confidence: 99%
“…Baobab oil is composed of 0.2-3% of Omega 3 (linolenic acid), 25-37% of Omega 6 (linoleic acid), 23-44% of Omega 9 (oleic acid), 1.5-6.0% of Stearic acid and 18-30% of Palmitic acid [12]. In many African regions, the oil is used as an analgesic for the treatment of pain (e.g., toothache), as anti-inflammatory, antioxidant, immune-stimulant, insect repellent, for treating wounds, varicose veins, muscle spasm, dysentery and diarrhea [13,14]. When used with coconut oil, the mixture can be used for the production of antibacterial soap to be applied on skin lesions such as eczema, acne, rashes and sunburn.…”
Section: Introductionmentioning
confidence: 99%
“…Baobab oil is a powerful emollient that nourishes, hydrates and conditions the skin, scalp and nails, it helps reduce stretchmarks and improves skin elasticity through the restoration of the skin and rejuvenation of the epithelial tissue. This explains why the oil is recommended during pregnancy [14][15][16]; the high concentrations of Omega 6 and 9 found in the oil stimulates synthesis of collagen and elastin fibers, promoting flexibility, firmness and smoothness while inhibiting inflammation [17,18]. Baobab oil has a strong oxidative stability and a long shelf life, its refractive index and iodine value range from 1.4596 to 1.4633 and 55 to 96 mg/100 g, respectively [17][18][19].…”
Section: Introductionmentioning
confidence: 99%